2016
DOI: 10.18632/oncotarget.9682
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent, truncating SOX9 mutations are associated with SOX9 overexpression, KRAS mutation, and TP53 wild type status in colorectal carcinoma

Abstract: PurposeThe extent to which the developmental transcription factor SOX9 functions as an oncogene or tumor suppressor in colorectal carcinoma (CRC) is debatable. We aimed to clarify the effect of SOX9 mutations on SOX9 protein expression and their association with known molecular subtypes and clinical characteristics in advanced CRC.Experimental DesignNext generation sequencing data (MSK-IMPACT) from CRC patients was used to interrogate SOX9, KRAS, NRAS, BRAF, TP53, APC, and PIK3CA. Mutant and wild type (WT) SOX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 18 publications
5
23
0
Order By: Relevance
“…43 Moreover, a variety of studies demonstrated that SOX9 was overexpressed in colon cancer tissues and cell lines compared with healthy colon epithelia, suggesting that SOX9 was inclined to be oncogenic in colon cancer. 36,37,42,44,45 In our study, we found that SOX9 was a downstream target for miR-30-5p, and LEF1-AS1 overexpression increased the expression level of SOX9 in colon cancer cells. Moreover, restoration of SOX9 attenuated the effects caused by LEF1-AS1 knockdown.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…43 Moreover, a variety of studies demonstrated that SOX9 was overexpressed in colon cancer tissues and cell lines compared with healthy colon epithelia, suggesting that SOX9 was inclined to be oncogenic in colon cancer. 36,37,42,44,45 In our study, we found that SOX9 was a downstream target for miR-30-5p, and LEF1-AS1 overexpression increased the expression level of SOX9 in colon cancer cells. Moreover, restoration of SOX9 attenuated the effects caused by LEF1-AS1 knockdown.…”
Section: Discussionsupporting
confidence: 49%
“…41 However, study of the truncating mutations of SOX9 indicating that these mutations were likely oncogenic and overexpressed in colon cancer. 42 Besides, data across TCGA showed that SOX9 was mutated and amplified in multiple cancers and whole gene deletion was rarely detected, a pattern typically seen in oncogenes. 43 Moreover, a variety of studies demonstrated that SOX9 was overexpressed in colon cancer tissues and cell lines compared with healthy colon epithelia, suggesting that SOX9 was inclined to be oncogenic in colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, SOX9 with up-regulated expression was indicated poor prognosis in colorectal cancer, glioma and lung cancer (Liu et al 2017 ; Bruun et al 2014 ; Zhou et al 2012 ). SOX9 over-expressed in colorectal cancer was reported by (Javier et al 2016 ; Montorsi et al 2016 and Shi et al 2015 ). However, the mechanisms underlying SOX9 mediated tumorigenesis remain elusive.…”
Section: Introductionmentioning
confidence: 79%
“…SOX9 displays missense or frameshift mutations in almost 10% of CRC [29]. SOX9 mutation rate is higher in more advanced tumors and is correlated with activated KRAS, an oncogene frequently mutated during CRC development, thus facilitating transformation and tumor progression [29]. Furthermore, a SOX9 splice variant (MiniSOX9) that contains the HMG domain responsible for binding to DNA but devoid of the trans-activating domain has been discovered [30].…”
Section: Sox9mentioning
confidence: 99%